The Relationship of Knowledge About Puberty with Adolescents Attitude in The Face of Puberty in Adolescents in Junior High School 3 Depok, Maguwoharjo, Sleman, Yogyakarta - Dwi Agustiana Sari; Wiwin Lismidiati; Melcyanus Patut (Journal of Health (JoH), 2016)
Background : Adolescence is a period of transition charaterized by a change in the physical,emisional, and psychological. At puberty occurs maturation of human reproductive organs. The need for knowledge and attitudes of adolescents about puberty in the face of the changes that occur are physical and psychological changes. Purpose : To be able to determine the relationship of knowledge about puberty in adolescent attitude in the face of puberty. Method : This study uses an analytical cross sectional design, Sampling with purposive sampling technique. Research sample totaled 124. The data were analyzed using chi square. Result : As many as 111 people ( 89, 5% ) havw a good level of knowledge about puberty.Adolescent attitude in the face of puberty in supporting categories, namely 114 ( 91,9% ). There is a significant relationship between the variables knowledge with attitude in the face of pubertaladoleschents in junior high school class VII 3 depok, Maguwoharjo, Sleman, Yogyakarta ( p= 0,001) Conclusion : There is a significant relationship between the variables knowledge with attitude in the face of pubertal adolescents in junior high school class VII 3Depok, Maguwoharjo, Sleman, Yogyakarta.